The Echinoderms of Aldabra and their habitats - Sloan, N. A.; Clark, A. M.; Taylor, J. D. (Bull. Br. Mus. Nat. Hist., 1979)
This first full account of the echinoderm fauna of Aldabra Atoll, western Indian Ocean, includes a description of the shallow-water habitats and two special ecological studies dealing with the microhabitats of the Ophiocomidae - the dominant family of coral-reef ophiuroids - and a comparison between the echinoderms of an exposed and sheltered part of the shore. The remainder consists of an annotated fauna list, with details of habitats, colours in life, parasites, commensals and other observations by Sloan, but also takes account of prevoius work by others at the Royal Society's base on the atoll. Nearly 130 species are included, of which 20% are recorded for the first time from the Islands of the western Indian Ocean (excluding the Mascarene Islands)